2016
DOI: 10.1186/s40200-016-0226-x
|View full text |Cite|
|
Sign up to set email alerts
|

Does this patient have Pheochromocytoma? a systematic review of clinical signs and symptoms

Abstract: ContextPheochromocytoma is a rare disease but with high mortality if it is not being diagnosed early. Several biochemical tests with high accuracy have been obtained, but the clinical threshold for request of these tests is not determined clearly.ObjectivesTo determine the Likelihood Ratios of clinical symptoms and signs in diagnosing pheochromocytoma. And also meta-analysis of their sensitivity in this disease.Data sourcesMEDLINE was searched for relevant English-language articles dated 1960 to February 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 38 publications
1
41
2
1
Order By: Relevance
“…Similarly, within the last month prior study enrollment, a relevant number of these patients reported on at least four of the pre-defined symptoms that had been associated with catecholamine excess (headache, sweatiness, palpitations, pallor, flush, panic, constipation, nausea, chest pain, abdominal pain, tremor and weakness). In a recent meta-analysis on the – often retrospective – literature of PPGL-related signs and symptoms, no single clinical feature could be identified with a particular value in diagnosing or excluding PPGLs ( 22 ). However, while prospective studies involving comparisons to patients in whom PPGL had been excluded will be required, it seems prudent that a high symptomatic burden should raise clinical suspicion for the presence of catecholamine excess.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, within the last month prior study enrollment, a relevant number of these patients reported on at least four of the pre-defined symptoms that had been associated with catecholamine excess (headache, sweatiness, palpitations, pallor, flush, panic, constipation, nausea, chest pain, abdominal pain, tremor and weakness). In a recent meta-analysis on the – often retrospective – literature of PPGL-related signs and symptoms, no single clinical feature could be identified with a particular value in diagnosing or excluding PPGLs ( 22 ). However, while prospective studies involving comparisons to patients in whom PPGL had been excluded will be required, it seems prudent that a high symptomatic burden should raise clinical suspicion for the presence of catecholamine excess.…”
Section: Discussionmentioning
confidence: 99%
“…The triad of pheochromocytoma (58%) is also sensitive but presents in only a few patients. [5] Truly, there is no single clinical i nding that can dei ne pheochromocytoma, but a good clinical judgment accompanied by thorough workup is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of hypertension was assigned to patients stated to have such a diagnosis or described as being on anti-hypertensive medications. Classical PHAEO symptoms were defined as the presence of any of the followings: headaches, palpitations and sweating ( 9 ). We looked into the patients demographics, mode of presentation and the occurrence of death, metastases or any adverse cardiovascular complications attributed to hypertensive crisis or circulating catecholamines.…”
Section: Methodsmentioning
confidence: 99%